Upaya Penegakan Hukum Dalam Mengatasi Penipuan Berbasis Operandi Hipnotis (Gendam) - Moch. Rifqi Mahfudhi; Ghazi Muhammad Tsany (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Hypnosis-based deceptive practices, commonly known as "gendam," have emerged as a growing concern in society. This article aims to examine the law enforcement efforts that can be employed to address these fraudulent activities. The research utilizes legal analysis and case studies to assess existing laws and regulations while identifying challenges faced by law enforcement agencies in combating gendam practices. The findings reveal that gendam practices are often challenging to detect and legally prove due to their covert and intangible nature. However, law enforcement efforts can be enhanced through increased public awareness regarding the dangers of gendam practices, training for law enforcement officers in identifying such criminal activities, and improvements in business oversight and related regulations. The article also reviews several legal cases associated with gendam practices that have been successfully prosecuted, illustrating how effective law enforcement can serve as a deterrent to perpetrators. Thus, this article provides insights into law enforcement strategies that can be employed to combat hypnosis-based deceptive practices (gendam) and underscores the need for collaboration between the public, government authorities, and law enforcement agencies to effectively address this issue.